Pedagogia inaciana e educação inclusiva: do que estamos falando? - Meneses, Amanda Viana (Universidade do Vale do Rio dos Sinos, 2021)
This study sought to address how the Ignatian Pedagogue favors Inclusive Education in promoting the integral education of the student, being a work of bibliographical research, considering studies of different texts, analysis of arguments, already existing by some theorists who spoke on the subject, as per for example, in Ignatian Pedagogy Luiz Fernando Klein, Fernando Hernández and Inclusive Education the main laws that govern them in our country and some authors such as Maria Salete Fábio Aranha, among others. Inclusion needs to be seen as a tool for social transformation, being aware that all students, regardless of their particularities, when they live and share the same spaces, are able to understand and accept each other, creating bonds such as friendship and respect, thus contributing to the construction of a fairer and more solidary society. Knowing that Ignatian Pedagogy contemplates a Christian vision of the world and of the human being, as its global and personalized process, the integral formation of the student comprises the learning of the whole person, in its wide dimensions, with the purpose of forming human conscience for the challenges of your time, it is therefore important to know this relationship that will become significant along the way.
Keywords: Pedagogia inaciana; Educação inclusiva; Educação integral; Ignatian pedagogy; Inclusive education; Integral education